(untitled) (Asian Journal of Medical Sciences, 2017)
It is well documented that infectious pathogen burden and infected cell mass determine the clinical severity of infectious diseases, however, the ability of the host to recognize and process antigens to produce antibodies or the cellular immune response during infection could be under genetic control. The Major Histocompatibility Complex (MHC) or Human Leukocyte Antigen (HLA) system is the most intensively studied of all genetic systems because of its influence to many important traits, including resistance to infectious diseases, autoimmunity and immunological self or nonself compatibility. This is understandable in the light of the evolutionary pressure so that we are equipped to face the multitude of infectious challenges. Infectious diseases are a major selective pressure;and genes involved in the immune response are the most numerous and diverse in the human genome; reflecting the evolutionary advantages of a diverse immunological response to a wide range of infectious pathogens. Asian Journal of Medical Sciences Vol.8(2) 2017 1-13